Evaluating Design Fiction for Requirements Elicitation in a Digital Game: An Exploratory Experimental Study - Leifheit, Bhruno Roan; Ceolin Júnior, Cassio; Ferreira, João Paulo Merlugo; Oliveira, Alessandreia; Vilela, Ricardo; Valle, Pedro; Silva, Williamson (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Context: Developing digital games is complex, requiring more than technical skills—it also involves capturing emotional and creative elements. This makes Requirements Engineering (RE) for games especially challenging, as traditional techniques often fail to address these aspects, causing gaps between developers and players. Objective: We explore Design Fiction as an alternative approach to support professionals in the game requirements elicitation process. Design Fiction combines design, science, and fiction to examine possible scenarios through narrative artifacts and diegetic settings. Methodology: An exploratory study employed Design Fiction and the Technology Acceptance Model (TAM) based questionnaires to assess professionals’ perceptions of a technique in early Survival Horror game design. Results: Results indicated high acceptance and engagement. Design Fiction proved effective in fostering creativity, clarifying expectations, and supporting collaboration, making it a valuable approach for eliciting experiential and emotional requirements in game RE.